A resource limited parallel program model - Rahozin, D.V. (Проблеми програмування, 2019)
Modern parallel programs run in a complex, resource-limited environment, and this raises the new requirements for resource consumption and execution stability of long running processes. In order to help with checking resource constraints for such parallel software a resource-limited parallel program formal model was developed. The model expresses the resource and time constraints and is suitable both for fine grained and coarse-grained parallelism in programs. For higher degrees of parallelism (at independent procedure level, bigger loop iterations, large computing blocks for graphics, video and neural network processing) the interpretation of formal model can be done in run-time and avoid dead locks and hangs during resource allocation. We are discussing several modern software frameworks that are able to integrate the functionality to interpret the model and check the feasibility of the set of parallel programs running on hardware simultaneously with resource and time limitations. Real world tasks – neural network inference, video processing, general purpose computing on GPU – which get benefits after enabling such models - are discussed.